Sticky Prices : An Empirical Assessment of Alternative Models - Jadresic, Esteban (IMF Working Papers; Working Paper ;, 1999)
This paper presents a model of staggered price setting that allows for a flexible distribution of the durations of the prices underlying aggregate price behavior, and estimates it with U.S. data. When tested against an unrestricted version of this model, standard models of sticky prices are rejected. In contrast, a stylized model that assumes a trimodal distribution of price durations-with clusters on the first, fourth, and eighth quarter after prices are set-easily passes the same test. In addition, this model is able to replicate the dynamic behavior of inflation and output found in the data.